Western Armenian Reality in Arandzar’s Satirical Novels - KARAPETYAN, SATENIK (Bulletin of Yerevan University B: Philology, 2021)
The purpose of our article is the consideration of the ways of expressing satire in Arandzar's short stories, which demonstrate Western Armenian reality during the end of XIX – the beginning of XX centuries. The unity of oppositions of comedy and tragedy, sorrow and laughter is the most characteristic line of Arandzar's satire. This is an ideological phenomenon and turns into a systematized way of thinking. The target of Arandzar's satire is different aspects of Western Armenian literary, social and political life of his time, which distorts the mentality and psychology of the Armenians who live under the Turkish yoke. In his short stories, sharp satire is directed against the Turkish arbitrariness, the legal system, the impunity of the rulers on the one hand, on the other hand, the writer with no less acutesatire criticizes the cowardice of rich Armenians, their indifference to their own people.
Keywords: satire, mockery, irony, laughter, sarcasm, ironic epithet, Western Armenian political life, tragic, comical, short story